Flood Detection Tool Using Ultrasonic Sensor Based on Telegram and Sound in Krueng Kluet River Flow - Ilham, Dirja Nur; Candra, Rudi Arif; Fardiansyah, Fardiansyah; Sipahutar , Erwinsyah; Budiansyah, Arie (PERFECT: Journal of Smart Algorithms, 2024)
Flooding is a problem that until now still requires special handling from various parties, both from the government and the community. Flooding is not a light problem because flooding can disrupt community activities and cause losses, such as the washing away of household equipment, valuables, and electronic goods. Flooding occurs due to rising water levels in rivers due to abnormal rainfall, damaged dams, obstruction of water flow at the site of the dam's destruction in the River Basin Area (DAK), and the construction of facilities and infrastructure. The series of "Flood Detection Devices using Ultrasonic Based on Telegram and Sound consists of three parts, namely the input section, the control section, and the display section. This design was made to simplify the process in the Ultrasonic Flood Detection Device Design using telegrams and sound. The Ultrasonic Flood Detection Device Design Circuit using telegrams and sound consists of three parts, namely the input section, the control section, and the display section. The first Flood Detection Device Test using Ultrasonic Sensors Based on Telegram and Sound has been tried as many as 10 The first experiment The water depth is 1 meter, the distance of the sensor to the water surface is 3 meters, it is said that the status is safe, there is no notification to the telegram and the siren does not sound. Experiment 2: The water depth is 2 meters, the distance of the sensor from the water surface is 2 meters, it is said to be on standby, then the flood detector provides notification to the telegram via the telegram bot, and the siren sounds. Experiment 3: The water depth is 3 meters, the distance of the sensor from the water surface is 1 meter, it is said to be on standby, then the flood detector provides notification to the telegram via the telegram bot, and the siren sounds.